Odpowiedzi

2009-09-05T20:17:18+02:00
4ײ+1,6y³-0,5ײ-y³+2,5=3,5x²+0,6y³+2,5

(8xyz-3ײ-yz)-(xyz-ײyz)+12=8xyz-3ײ-yz-xyz-x²yz=7xyz-3ײ-yz-x²yz

9a²+[7a²-2a-(a²-3a)]+(-5+a²)=9a²+7a²-2a-a²+3a-5+a²=16a²+a-5
Najlepsza Odpowiedź!
2009-09-05T20:17:52+02:00
4ײ+1,6y³-0,5ײ-y³+2,5=3,5x²+o,6y³+2,5

nie pamietam jak sie robiło z nawiasami
2009-09-05T22:01:23+02:00
4ײ+1,6y³-0,5ײ-y³+2,5=
3,5x²+0,6y³+2,5

(8xyz-3ײ-yz)-(xyz-ײyz)+12=
8xyz-3x²-yz-xyz+x²yz+12=
7xyz-3x²-yz+x²yz+12

9a²+[7a²-2a-(a²-3a)]+(-5+a²)=
9a²+[7a²-2a-a²+3a]-5+a²=
9a²+7a²-2a-a²+3a-5+a²=
16a²-a-5